Arctic Entrepreneurship and Supply Chain Strategy Integration as Part of Creative Economy - Natalya Ivanovna Petrova; Alexandra Vasilievna Fedorova; Natalya Nikolaevna Petrova; Natalya Nikolaevna Alekseeva (International Journal of Supply Chain Management, 2019)
The Arctic regions with their rich but almost inaccessible natural resources are in the focus of attention of nation states and global business. Problems and potential of sustainable socio-economic development are determined by national priorities, the economy and infrastructure of the Arctic. Interaction of the supply chain strategy and entrepreneurship can unlock the potential of the Arctic through the stimulation of supply chain management and entrepreneurship as a key objective in the development of the region. In this regard, it is crucial to create conditions for developing the labor market based on creative competencies and digital technologies, and the solution of this task will increase the income of the indigenous people. Doing this research, the authors used the results of the studies on the economy of the Arctic regions and the data on the Russian Arctic of the State Statistics Committee of the Russian Federation. Its economic structure includes traditional sectors: reindeer husbandry, hunting, and fishing. Industrial, transport, and energy development of the territories have a negative impact on traditional activities, so that the peoples of the Arctic have to search for new forms and ways of employment, conservation of the environment, and ethno cultural development. The results of expert questionnaires and surveys of the people living in the Arctic regions of the republic indicate the interest of the Arctic population in self-employment and working in tourism as a way of earning their living.